2014
DOI: 10.1089/scd.2013.0600
|View full text |Cite
|
Sign up to set email alerts
|

let-7Enhances Osteogenesis and Bone Formation While Repressing Adipogenesis of Human Stromal/Mesenchymal Stem Cells by Regulating HMGA2

Abstract: Bone and fat cells share a common progenitor, stromal/mesenchymal stem cells (MSCs), that can differentiate into osteoblasts or adipocytes. Osteogenesis and adipogenesis of MSCs maintain homeostasis under physiological conditions. The disruption of this homeostasis leads to bone-related metabolic diseases. For instance, reduction in bone formation, which is usually accompanied by an increase in bone marrow adipogenesis, occurs with aging, immobility, or osteoporosis. Thus, it is crucial to gain an understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 47 publications
(65 reference statements)
8
122
1
Order By: Relevance
“…Indeed, it was reported that let-7 levels are increased during osteogenic lineage commitment of mesenchymal stem cells [55], and that ectopic expression of let-7 enhances osteoblast formation in vitro and in vivo by targeting HMGA2 [27]. Our in vitro data confirmed these effects in both donors on the level of ALP expression and in one donor on the level of Alizarin staining.…”
Section: Limitations Of the Studysupporting
confidence: 83%
“…Indeed, it was reported that let-7 levels are increased during osteogenic lineage commitment of mesenchymal stem cells [55], and that ectopic expression of let-7 enhances osteoblast formation in vitro and in vivo by targeting HMGA2 [27]. Our in vitro data confirmed these effects in both donors on the level of ALP expression and in one donor on the level of Alizarin staining.…”
Section: Limitations Of the Studysupporting
confidence: 83%
“…It was reported that H19 also served as a competing endogenous RNA for the let-7 family of microRNAs and its deletion resulted in overexpression of let-7 [40]. Moreover, let-7 has been showed to enhance osteogenesis and suppress adipogenesis by negatively regulating high mobility group AT hook 2 ( HMGA2 ) in ASCs [41]. Therefore, we attempted to determine whether H19 could act as a molecular sponge for let-7 to regulate the function of HMGA2 in ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, let-7-mediated repression of adipogenesis was also found to promote osteogenesis [58]. HMGA2 and let-7 have been found be important regulators of tumor growth and are known to be dysregulated in lipomas and liposarcomas from human patients [59, 60].…”
Section: Mirnas Regulating Pre-adipocyte Clonal Expansionmentioning
confidence: 99%